BAHASA INDONESIA DAN DAERAH DALAM PERSPEKTIF PENDIDIKAN DI BANTEN - Dase Erwin Juansah (Jurnal Membaca Bahasa dan Sastra Indonesia, 2016)
Indonesian  Language  has  two  positions,  namely  as  the  national  language  and  the language of the State. In his position as the national language, Indonesian Language serves as a symbol of national pride, a symbol of national identity and as a means of communication between peoples, inter-region and intertribe. Meanwhile, as the language of the state serves as the language of instruction in educational institutions, official state language, national cultureof developer tools, science and technology. The Political Language Seminar in 2000 decided that the position of regional languages serve as a symbol of regional pride, regional identity and local community relations. The presence of Indonesian and regional languages at the present time has begun to erode in the presence of a foreign language. At least, the languageusers  are  no  longer  using  language  appropriate  to  the  place  and  the  circumstances. Sometimes in a formal situation, people are using foreign languages or regional languages, although the situation is demanding to use Indonesian. The same thing happened in the contextof education in Banten province, the vast majority of students and educators in the teaching and learning process in the classroom often use or mix the language with the local language in Indonesian or foreign language. One of the factors that caused the decline in the vitality ofIndonesian Language in society and in educational institutions is the linguistic competence of the speakers, thus when doing communication, they mix or even leave Indonesian Language.